A novel way for hydroxyl radicals generation: Biochar-supported zero-valent iron composite activates oxygen to generate hydroxyl radicals. Issue 4 (August 2022) - Duan, Linshuai; Liu, Xinhui; Zhang, Handan; Liu, Fei; Liu, Xiqin; Zhang, Xin; Dong, Lu
Abstract: As the cheapest oxidant, it is significant to investigate how to use oxygen to generate hydroxyl radicals (· OH) effectively. Though the oxidation of zero-valent iron (ZVI) by O2 can generate · OH, the yield is too low for application. Here, we successfully prepared the biochar-supported zero-valent iron composites (BC-ZVI) and applied them to generate · OH. The · OH quantitative experiments presented that the BC-ZVI (1:1) has the strongest ability to activate oxygen to generate · OH among the different mass ratios of BC-ZVI, which can reach 20.19 μM at the concentration of 1.0 g/L. Materials characterization results demonstrated that the uniform dispersion of ZVI particles and the catalytic capacity of biochar led to the superior performance of BC-ZVI (1:1) in · OH generation. The O2 · - and H2 O2 are proved to be the intermediate reactive oxygen species in the generation of · OH through reactive oxygen species (ROS) capture experiments. Our findings presented that the BC-ZVI (1:1) exhibited high performance in TC removal (186.26 mg/g) and the role of · OH was demonstrated by quenching experiments. Overall, those results indicated that BC-ZVI (1:1) composite could be a promising material to generate · OH and remove pollutants. Graphical Abstract: ga1 Highlights: The · OH generation ability of BC-ZVI (1:1) is significantly higher than pristine BC and ZVI. The uniform dispersion of ZVI particles and the catalytic capacity of BC contribute to · OH generation. O2 · - and H2 O2 are the key intermediate reactive oxygen species in the generation of · OH. The TC removal ability of the BC-ZVI (1:1) composite is up to 186.26 mg/g.